Some general Kantorovich type operators - Braica, Petru I.; Pop, Ovidiu T. (Rev. Anal. Numér. Théor. Approx., 2012)
A general class of linear and positive operators of Kantorovich-type is constructed. The operators of this type which preserve exactly two test functions from the set \({e_0, e_1, e_2}\) are determined and their approximation properties and convergence theorems are studied.